2001
DOI: 10.1034/j.1600-0536.2001.440101.x
|View full text |Cite
|
Sign up to set email alerts
|

An update on airborne contact dermatitis

Abstract: ) were screened, and the cases cited were classified as to history, lesion locations, sensitization sources, and other factors. Reports on airborne dermatitis are increasingly being published, sometimes in relation to specific occupational areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
2
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 130 publications
0
35
2
3
Order By: Relevance
“…Multiple chemical exposures at very low concentrations are commonly present in the workplace and usually show positive reactions in the patient's skin patch test as reported in this study. Several studies have also reported that airborne contact is an important exposure route for ACD in addition to direct dermal contact [10][11][12][13]18) . We have falsified the airborne route as a possible exposure pathway by showing no allergic chemicals existing in the patient's workplace from our air monitoring results.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple chemical exposures at very low concentrations are commonly present in the workplace and usually show positive reactions in the patient's skin patch test as reported in this study. Several studies have also reported that airborne contact is an important exposure route for ACD in addition to direct dermal contact [10][11][12][13]18) . We have falsified the airborne route as a possible exposure pathway by showing no allergic chemicals existing in the patient's workplace from our air monitoring results.…”
Section: Discussionmentioning
confidence: 99%
“…La literatura científica recuperada, demuestra la asociación entre las DCAT y la presencia de sustancias irritantes en el lugar de trabajo 43 , en este caso, en la industria química, farmacéutica y en personal sanitario, reforzando el hecho de que nos encontramos ante una forma de presentación prevalente dentro de la patología dermatológica laboral 32 y demostrando el interés y la relevancia del tema a nivel médico-laboral.…”
Section: Discusión Y Conclusionesunclassified
“…Sensitization is seen in workers who handle unhardened epoxy resin [46,96]. As a result, the hands and the face are predominantly affected by eczema, the latter through airborne exposure [63,65].…”
Section: Epoxy Resinmentioning
confidence: 99%